2008
DOI: 10.1038/leu.2008.312
|View full text |Cite
|
Sign up to set email alerts
|

Specific cytogenetic abnormalities are associated with a significantly inferior outcome in children and adolescents with mature B-cell non-Hodgkin's lymphoma: results of the FAB/LMB 96 international study

Abstract: Clinical studies showed that advanced stage, high LDH, poor response to reduction therapy and combined bone marrow and central nervous system disease are significantly associated with a decreased event free survival (EFS) in pediatric mature B-NHL treated on FAB/LMB96. Although rearranged MYC/8q24 (R8q24) is characteristic of Burkitt Lymphoma (BL), little information is available on other cytogenetic abnormalities and their prognostic importance. We performed an international review of 238 abnormal karyotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
107
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 33 publications
14
107
1
Order By: Relevance
“…24 Even in pediatric patients with DLBCL, the presence of 8q24 rearrangements independently reduces event-free survival by 6-fold. 39 By contrast, Copie-Bergman and colleagues found that presence of MYC rearrangement did not predict shortened OS in DLBCLs treated with R-CHOP. 13 Half of our cases with MYC rearrangement also had BCL2 and/or BCL6 rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…24 Even in pediatric patients with DLBCL, the presence of 8q24 rearrangements independently reduces event-free survival by 6-fold. 39 By contrast, Copie-Bergman and colleagues found that presence of MYC rearrangement did not predict shortened OS in DLBCLs treated with R-CHOP. 13 Half of our cases with MYC rearrangement also had BCL2 and/or BCL6 rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly deleted band was 13q34 (82%). The relationship between karyotypic abnormalities and outcomes showed that + 7q and del(13q) were independently associated with a significant inferior event free survival (EFS) (hazard ratio: 2·5 (P = 0·015) and 4·0 (P = 0·0003) respectively) (Poirel et al, 2009), which agrees with prior reports suggesting a worse outcome associated with 13q abnormalities (Fig 3B, C) (Lones et al, 2004;Onciu et al, 2006). Subsequently, Nelson et al (2009) utilized FISH to show a worse overall survival in patients with any 13q deletion (Fig 4).…”
Section: Cytogeneticsmentioning
confidence: 99%
“…Additional recurrent chromosomal abnormalities have been recognized with chromosomes 1, 6, 13, 17, and 22 most commonly involved (Lones et al, 2004;Onciu et al, 2006). A large cytogenetic study performed on an international trial in children and adolescents with mature B-cell lymphoma further characterized the secondary genetic changes detectable by karyotyping (Poirel et al, 2009). The main BL-associated chromosomal aberrations were + 1q (29%), +7q (14%), and del(13q) (14%).…”
Section: Cytogeneticsmentioning
confidence: 99%
“…While the impact of additional cytogenetic abnormalities detected by conventional karyotype on clinical outcomes in Burkitt or Burkitt-like lymphomas has been the subject of several studies, [9][10][11] there is very little information regarding their diagnostic value in the classification of highgrade B-cell lymphomas. Although prompt diagnosis of Burkitt lymphoma and other high-grade B-cell lymphomas carrying MYC rearrangements is clinically important because they are aggressive and may require more intensive therapy, 12 the diagnosis sometimes can be challenging.…”
mentioning
confidence: 99%